Integrated procedure of meteorological classification of objects and estimation of their information parameters - Игнатов, В. А. (Proceedings of National Aviation University (archive), 1998)
Considered are the results of investigation of classification of methods and algorithm with given authenticity of meteorological objects received by radar sounding with point or interval estimation of the parameters of surveillance objects (for example, rain clouds). Shown is the use of method of statistic theory of hypothesis checking for classification of rain and shower clouds. The results of investigation can be used for working out conditions of radar remote sounding, calibration and testing of designed instruments and programme parts, means of maintenance support systems of radar sounding meteorological objects